2008
DOI: 10.1097/moh.0b013e328313e3bd
|View full text |Cite
|
Sign up to set email alerts
|

Glycans and glycosylation of platelets: current concepts and implications for transfusion

Abstract: Room temperature storage of platelet products increases the risk of transfusion-mediated sepsis and accelerates platelet deterioration, limiting platelet shelf life. Recent evidence suggests that glycoengineering of platelets might allow for their cold storage, significantly improving the quality of platelet products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…With the aim of using glycoengineering to prevent clearance of cold-stored platelets, we have shown that addition of the donor substrate UDP-Gal causes glycosylation of exposed GlcNAc residues on GPIb␣, preventing recognition of cold-stored platelets by the hepatic macrophage ␣M␤2 clearance system. 11,15,48 The present study demonstrates that platelet sialyltransferases transfer fluorescently labeled CMP-SA to specific platelet surface proteins, capping exposed galactose and preventing the clearance of platelets mediated by the hepatic asialoglycoprotein receptor. 29 These findings suggest that glycoengineering could prevent the recognition of cold-stored platelets using a combination of galactosylation and sialylation.…”
Section: Platelets Have Glycan Biosynthesis Capacity 633mentioning
confidence: 99%
See 1 more Smart Citation
“…With the aim of using glycoengineering to prevent clearance of cold-stored platelets, we have shown that addition of the donor substrate UDP-Gal causes glycosylation of exposed GlcNAc residues on GPIb␣, preventing recognition of cold-stored platelets by the hepatic macrophage ␣M␤2 clearance system. 11,15,48 The present study demonstrates that platelet sialyltransferases transfer fluorescently labeled CMP-SA to specific platelet surface proteins, capping exposed galactose and preventing the clearance of platelets mediated by the hepatic asialoglycoprotein receptor. 29 These findings suggest that glycoengineering could prevent the recognition of cold-stored platelets using a combination of galactosylation and sialylation.…”
Section: Platelets Have Glycan Biosynthesis Capacity 633mentioning
confidence: 99%
“…29 These findings suggest that glycoengineering could prevent the recognition of cold-stored platelets using a combination of galactosylation and sialylation. 48 Immature glycans could also represent essential clearance signals on activated circulating platelets, and it is tempting to speculate that reglycosylation of exposed immature glycans could prolong platelet survival. In support of this notion, desialylated GPIb␣ was shown previously to be a target for TACE (ADAM17), which inactivates VWF receptor function.…”
mentioning
confidence: 99%
“…4,10 As platelets lose sialic acid from membrane glycoproteins during aging and circulation, enhanced exposure of nonsialylated glycan chains may represent a physiologic phenomenon triggering clearance of senescent blood cells. [11][12][13] Observations that platelets with increased exposure of ␤Gal may serve as endogenous ligands for the ASGPR were recently substantiated in a study that demonstrated this clearance mechanism to induce thrombocytopenia during Streptococcus pneumoniae sepsis. 14 Sialyltransferases are a family of 21 characterized glycosyltransferases transferring sialic acid from the donor substrate CMP-sialic acid to acceptor oligosaccharide substrates.…”
Section: Introductionmentioning
confidence: 97%
“…The major drawbacks of storage at room temperature are the growth of bacteria, which contaminate one in 2,000 platelet units 1 and the decline in platelet viability and function known as platelet storage lesion. 2 Lowering the temperature to 0-4°C may be a better alternative, but this approach introduces new problems as it affects glycoprotein (GP) Ibα. GPIbα is the major subunit of the receptor for von Willebrand factor (VWF), which traps platelets at sites of vessel damage enabling firm attachment by collagen receptors GPVI and integrin α2b1.…”
Section: Introductionmentioning
confidence: 99%